2014
DOI: 10.1007/s00467-014-2871-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of direct radionuclide cystography in the detection of vesicoureteral reflux in children with normal voiding cystourethrography

Abstract: Based on our results, we suggest that DRNC may reveal VUR despite a normal VCUG in children with hydronephrosis, abnormal acute DMSA, and/or recurrent febrile UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Direct radionuclide cystography is a sensitive method and has lower radiation dose compared to voiding [7] however,, do not provide anatomical detail thus not preferred as first imaging method in the male patients at the first diagnosis. In a recent comparative study the direct radionuclide methods has been found to be more correlated with DMSA findings and clinical results [8]. The DMSA scan findings of the patients are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…Direct radionuclide cystography is a sensitive method and has lower radiation dose compared to voiding [7] however,, do not provide anatomical detail thus not preferred as first imaging method in the male patients at the first diagnosis. In a recent comparative study the direct radionuclide methods has been found to be more correlated with DMSA findings and clinical results [8]. The DMSA scan findings of the patients are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 97%
“…RNC requires catheterization, but less radiation exposure than VCUG. Although continuous monitoring is available, the details on the film are not more precise than VCUG, although RNC might show occult VUR, which cannot be detected by VCUG in children with hydronephrosis, abnormal acute DMSA and/or recurrent febrile UTI . Generally, the main advantage of RNC is that the patient is exposed to only one‐tenth of the radiation required for VCUG .…”
Section: Are There Any Alternatives To Vcug?mentioning
confidence: 99%
“…Although continuous monitoring is available, the details on the film are not more precise than VCUG, although RNC might show occult VUR, which cannot be detected by VCUG in children with hydronephrosis, abnormal acute DMSA and/or recurrent febrile UTI. 134 Generally, the main advantage of RNC is that the patient is exposed to only onetenth of the radiation required for VCUG. 135 Recent techniques to reduce radiation exposure, such as the digital grid-controlled, variable rate and pulsed acquisition technique, are also available.…”
Section: Rncmentioning
confidence: 99%
“…Vesicoureteral reflux (VUR), most important predisposing factor for UTI, may consequently lead to the complications such as renal scarring, hypertension, and chronic renal failure. Direct radionuclide voiding cystography (DRNC), the procedure causing 50-to 100-fold less radiation exposure to the gonads and bladder than VCUG 26) , is helpful in diagnosis and follow-up of patients with VUR with higher sensitivity and higher temporal resolution than VCUG 27) , even though accurate anatomical information of urethra and bladder and degree of reflux cannot be provided with DRNC. Besides its poor image resolution, DRNC has not been widely used probably because most urologists are familiar with the radiologic grading system 28) .…”
Section: Vericoureteral Refluxmentioning
confidence: 99%